A provably secure certificateless organizational signature schemes. (18th August 2015) - Allam, Ali M.; Ali, Ihab A.; Mahgoub, Shereen M.
Summary: 'Organization signature is a new variant of digital signature in organization transactions. It allows the employee in the organization to generate the message signature through his affiliation rather than his personal description. Certificateless public key cryptography solved the key escrow problem in identity‐based cryptography, and the certificate distribution in the traditional public key infrastructure. In this paper, we present a provable secure pairing‐free certificateless organizational signature scheme. Our scheme is more computationally efficient because it does not depend on pairings. The new scheme is provably secure in the random oracle model, assuming the hardness of elliptic curves discrete logarithm problem.' Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Organization signature is a new variant of digital signature in organization transactions. It allows the employee in the organization to generate the message signature through his affiliation rather than his personal description. In this paper, we present a provable secure pairing‐free certificateless organizational signature scheme. Our scheme is more computationally efficient because it does not depend on pairings. The new scheme is provably secure in the random oracle model, assuming the hardness of elliptic curves discrete logarithm problem.